Predictors of insomnia among undergraduate students at Hawassa University Sidama, Ethiopia, 2023: a facility-based cross-sectional study - Aschale Wale, Mastewal; Reta, Yared; Addis, Haymanot; Tarekegn, Rahel; Tafese, Mintesnot; Tsega Chekol, Aklile (Frontiers in Psychiatry, 2024)
Background: Insomnia is a sleep disorder characterized by difficulty falling asleep, staying asleep, or experiencing poor-quality sleep. People with this problem often have trouble falling asleep at night, wake up frequently during the night, and may wake up too early in the morning and feel tired with no refreshed. This can lead to daytime fatigue, irritability, difficulty concentrating, and impaired functioning in their day-to-day activities. Study is scarce in the resource-limited country including Ethiopia, particularly in the study setting. As a result, this study aimed to assess the prevalence of insomnia and its associated factors among, undergraduate students at Hawassa University.Methods: An institutional-based cross-sectional study design was used. A stratified simple random sampling method was used among 398 study participants. The data was collected using a structured self-administered questionnaire.The outcome variable was assessed by the insomnia severity index (ISI). The data was collected by using the Kobo toolbox online and then exported into a statistical package of Social Science version 27 to analyze the data. Data cleaning and screening were conducted exclusively by the investigators. Descriptive statistics like frequency, percentages, and mean were used. Bivariate and multivariate binary regression were performed. In multivariate binary logistic regression, a P value of < 0.05 was identified as a significantly associated factor with the dependent variable.Results: Among 398 students who participated in the study 81(20.4%) experienced insomnia. Being female (AOR=2.98; 95% CI 1.56-5.69), age (AOR=3.06;95% CI 1.11-8.45), mild anxiety symptom (AOR=4.89;95% CI 1.56-15.37), and mobile use ≥30 minutes just before going to sleep (AOR=7.81; 95% CI 2.34-26.12) were significantly associated with insomnia.In this study, the prevalence of insomnia was one-fifth among university students which is high when compared to another study at the national level. There were significant associations between being female, age, anxiety symptoms, and mobile device use before sleep with insomnia. This indicates there is a need to treat and prevent insomnia in college students, emphasizing the necessity for mental health care and ethical technology use.